Dielectric properties of BiFeO3-PbTiO3 thin films prepared by PLD - 陈蕊 俞圣雯 张冠军 程晋荣 孟中岩 (Transactions of Nonferrous Metals Society of China, 2006)
BiFeO3-PbTiO3 （BFO-PT） thin films were prepared on Pt/TiO2/SiO2/Si substrates by pulsed-laser deposition （PLD） technique under different oxygen pressures. The structures of the films were characterized by means of XRD. The current densities were performed to check the conductivity of the films. The dielectric constant and loss factor （tanδ） of the films were measured. The results show that the BFO-PT layers are mainly perovskite structured; the film deposited under 6.665 Pa exhibits low leakage current, low dielectric loss （0.017-0.041） and saturated hysteresis loop with polarization （Pr） value and coercive field （Ec） of 3 μC/cm^2 and 109 kV/cm.